"What" and "How": A New Perspective for Understanding Unawareness in Alzheimer's Disease Through a Combination of Two Perspectives. (5th June 2020) - Mayelle, Amandine; El Haj, Mohamad; Antoine, Pascal
Objectives: Assessments of unawareness in Alzheimer's disease mainly focus on the objects (the "what") of unawareness. A recent person-centered approach proposes to also assess the processes (the "how"). The present study combines 2 approaches to understand this heterogeneity in assessments of unawareness. Method: We recruited 46 participants from 8 nursing homes. They underwent a semi-structured interview and were assessed using a prediction–performance paradigm. Spearman correlations were calculated, and generalized additive models were established. Results: The 2 approaches are associated through cognitive deficits, confrontation with difficulties and identity changes. Objects (the what), mechanisms, and modes of expression (the how) explain at least 29.6% of the variance of unawareness. Conclusions: Unawareness is more than simply being unaware of something; it is a synergy between the objects and processes of arousal and expression. Moreover, unawareness extends beyond the disease to include the self. Considering the entire person seems to be necessary.